2007
DOI: 10.1002/art.23129
|View full text |Cite
|
Sign up to set email alerts
|

Can biochemical markers serve as surrogates for imaging in knee osteoarthritis?

Abstract: Objective. Osteoarthritis (OA) is a complex heterogeneous joint disease affecting more than 35 million people worldwide. The current gold standard diagnostic investigation is the plain radiograph, which lacks sensitivity. Biochemical markers have the potential to act as adjunct markers for imaging in the assessment of knee OA. We undertook this study to determine the association between individual biochemical markers and radiographic features, and to establish whether the association is strengthened when selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 53 publications
3
36
1
Order By: Relevance
“…It has also been reported other studies. 8,14,15 This might be because the comparable BMI of Case group and Control group in our study as the controls were siblings or first degree relatives of the patients in the same age group. On the contrary positive correlation between HA levels and BMI has also been reported.…”
Section: Discussionmentioning
confidence: 82%
“…It has also been reported other studies. 8,14,15 This might be because the comparable BMI of Case group and Control group in our study as the controls were siblings or first degree relatives of the patients in the same age group. On the contrary positive correlation between HA levels and BMI has also been reported.…”
Section: Discussionmentioning
confidence: 82%
“…In recent years, however, the trend has shifted from assessments of individual markers to uncovering clusters of markers that may correlate with disease progression and activity. Indeed, it was recently demonstrated, using an approach based on the association of selected biochemical markers combined into a single factor, that a combined panel of biochemical markers showed a stronger association with OA than any individual markers [118]. Moreover, their analysis also suggested that markers identifying patients with osteophytes overlapped those with a high Kellgren-Lawrence score while markers for BMD of the subchondral bone were uncovering a totally different group, hence raising the possibility that although osteophytes and subchondral BMD are associated with OA, they may have underlying biological differences.…”
Section: Bone Markers In Oamentioning
confidence: 99%
“…It appears that variation in peptides is more frequent in the low molecular weight (LMW) component of the sera of OA subjects. Earlier reports have also deduced that most of the variation in human proteome lies in the LMW region which is rich in cytokines, chemokines, peptide hormones and a few proteolytic fragments (35,47,50). We suggest further investigations in this direction to identify and characterize these novel LMW fractions present in the sera of OA subjects.…”
Section: Discussionmentioning
confidence: 53%
“…We have, therefore, selected sera as the potential source of chan ging proteomic profiles in subjects with osteoarthritis (OA). Various studies have identified potential biochemical markers as a means of diagnosing and monitoring OA, and investigators in some of these studies have reported radiographic assessment (35), hyaluronan (36), C-reactive proteins (37)(38), enzymes (20, 22-23, 25, 39-41) and many more (42)(43)(44)(45)(46). Even the estimation of absolute protein values provides relatively better options and puts forward the marker value of many useful protein fractions (16,33,35,47).…”
Section: Discussionmentioning
confidence: 99%